Analisis Pemalsuan Minyak Jinten Hitam (Nigella Sativa) Menggunakan Kombinasi Metode Spektrofotometri Inframerah dan Kalibrasi Multivariat - , RIZKA ARIANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Fourier Transform infrared spectrophotometry (FTIR) combined with multivariate calibration of partial least square (PLS) was developed and optimized for analysis of NSO in binary and ternary mixtures with CO and SO. Based on PLS modeling that has been conducted, quantitative analysis of NSO in binary mixtures with CO using second derivative spectral at combined frequencies of 2977-3028, 1666-1739, and 740-1446 cm-1 revealed the highest value of R2 (0.9984) and the lowest value of RMSEC (1.33). NSO in binary mixtures with SO is successfully determined at frequencies of 2985-3024 and 752-1755 cm-1 using first derivative FTIR spectra with R2 and RMSEC values of 0.9970 and 0.47, respectively. Meanwhile, first derivative spectral at frequencies of 2985-3024 and 752-1755 cm-1 was selected for quantitative analysis of NSO in ternary mixture with CO and SO with R2 and RMSEC values of 0.9997 and 0.47, respectively. The results showed that FTIR spectrophotometry is an accurate technique for quantitative analysis of NSO in binary and ternary mixtures with CO and SO.